The Relationship Between Self-Efficacy and Dietary Compliance in Patients with Diabetes Mellitus at Cancar Public Health Center: English - Hepilita, Yohana; Natul, Fransiska Kurniati; Angelina, Rena Putri Theresia (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2025)
Dietary regulation is one of the main pillars in the management of diabetes mellitus. Effective dietary management requires strong commitment and self-discipline from patients to achieve optimal outcomes. This study aimed to examine the relationship between self-efficacy and dietary compliance among patients with diabetes mellitus at Cancar Public Health Center, Manggarai Regency. A quantitative approach with a cross-sectional design was employed, using a total sampling technique involving 30 respondents. Data were analyzed using Kendall’s Tau-b correlation test. The findings revealed that among respondents with high self-efficacy, 13 were compliant with their diet and 2 were less compliant. Among those with moderate self-efficacy, 1 was compliant, 5 were less compliant, and 4 were non-compliant. Meanwhile, respondents with low self-efficacy showed no compliance or low compliance, with 5 individuals categorized as non-compliant. The statistical analysis using Kendall’s Tau-b test demonstrated a significant relationship between self-efficacy and dietary compliance (ρ-value = 0.000). These results suggest that improving self-efficacy in patients with diabetes mellitus is essential to enhance dietary adherence and prevent more severe health complications.